Penegakan Hukum Terhadap Influencer Sebagai Wajib Pajak Penghasilan yang Tidak Memiliki Nomor Pokok Wajib Pajak (NPWP) - A. A. Ayu Ningrat Chuk Putri Prameswari; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2025)
The advancement of today's times and increasingly advanced technology indirectly also develops new income and businesses, including social media Influencers. The amount of income they get classifies Influencers as tax subjects. From the income earned by the Influencers, many of them do not fulfill the tax provisions, especially not having a Taxpayer Identification Number, which is for tax administration facilities. This research has two problem formulations, namely how the legal regulation of Influencers as taxpayers and how legal sanctions against Influencers as income taxpayers who do not have NPWP. This research uses normative legal research. This research results in a discussion regarding the activities carried out by Influencers on social media can be taxed by the government in accordance with the Income Tax Law because it is an economic activity that can generate large profits. Influencers who do not have a Taxpayer Identification Number are a form of tax evasion and can be subject to sanctions in accordance with Law No. 28 of 2007 concerning General Provisions and Tax Procedures.